2015
DOI: 10.1016/j.adolescence.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the cross‐cultural validity of the Identity Capital Model: American and Japanese students compared

Abstract: The Identity Capital Model proposes that forms of personal agency are associated with identity development as part of the transition to adulthood. This model was examined in two cultural contexts, taking into account age and gender, among college and university students aged 18 to 24 (N ¼ 995). Confirmatory Factor Analyses verified cultural, age, and gender invariance of the two key operationalizations of the model. A Structural Equation Model path analysis confirmed that the model applies in both cultures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…For example, locus of control has been found to differentially predict human behaviors in different cultural contexts. Côte, Mizokami, Roberts, and Nakama (2016) found that college students in the United States had a higher internal locus of control than their counterparts in Japan, and internal locus of control was a predictor of identity development only for American but not for Japanese students. Furthermore, locus of control has been found to be related to vocational outcome expectations among undergraduate students in Turkey (Işik, 2013) and job satisfaction among adults in Australia (Wu, Griffin, & Parker, 2015) and China (Guan et al, 2012).…”
Section: Directions For Future International Scct Researchmentioning
confidence: 95%
“…For example, locus of control has been found to differentially predict human behaviors in different cultural contexts. Côte, Mizokami, Roberts, and Nakama (2016) found that college students in the United States had a higher internal locus of control than their counterparts in Japan, and internal locus of control was a predictor of identity development only for American but not for Japanese students. Furthermore, locus of control has been found to be related to vocational outcome expectations among undergraduate students in Turkey (Işik, 2013) and job satisfaction among adults in Australia (Wu, Griffin, & Parker, 2015) and China (Guan et al, 2012).…”
Section: Directions For Future International Scct Researchmentioning
confidence: 95%
“…Identity resolution. The Identity Resolution Scale (Côté, Mizokami, Roberts, & Nakama, 2016) is composed of two subscales, one assessing adult identity resolution (3 items, e.g., "You consider yourself to be an adult," a ¼ .83) and the other assessing societal identity resolution (3 items, e.g., "You have settled on a lifestyle that you are satisfied with for the remainder of your life," a ¼ .70).…”
Section: Methodsmentioning
confidence: 99%
“…The Identity Capital Model places individualisation in the context of maturation prolonged by continuing education and training (Côté 2002;Côté et al 2016). Identity capital for Côté 2002is those resources available internally (intangible identity capital) and externally (tangible identity capital) which aid a young person's navigation between extremes of structured/unstructured identity formation.…”
Section: Identity Capitalmentioning
confidence: 99%